Evolution of the anticoagulant treatment. “From tick and leech to pill” - Bednarek, Wiesława; Radziejewicz, Paweł; Sobstyl, Małgorzata; Bednarek, Andrzej (Menopause Review/Przegląd Menopauzalny, 2010)
This study shows short heparin characteristics used in venous thromboembolism. The research history and the way of selected heparin synthesis are shortly described. The sequence of drugs showed in the study is based on their chronological introduction into medical practice.